SOME CURIOUS FINDINGS HAIR FOLLICLES BIOELECTROMAGNETIC RADIATION EXPRESSED AS LIGHT DISPLACING MATTER IN ITS PATH AND THE CONTRALATERAL EMISSION OF MAGNETIC FIELDS FOUND IN THE HAIR SHAFT - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2021)
BACKGROUND In physics the term light refers to electromagnetic radiation, which includes visible light, which has also been described as exerting physical pressure on matter in its path; this could be explained by the “particle nature of light”. To date light rays emission experiments has been done mainly on non-living matter. This manuscript will show in vitro results where biological tissue (hair follicles) is shown emitting electromagnetic radiation in a light form and displacing particles in its path. Additionally the hair shaft one-sided biomagnetism is shown. METHODS A mini-review of prior experiments by this author and others are herein presented where bioelectromagnetic fields expressed as light are shown displacing matter of ferric cyanide chemical compounds. A seminal paper published in 1980, is also included where human hair follicles had been documented as emitting magnetic fields when applying pressure on the human scalp. RESULTS Findings are presented where light rays or flashes emitted by hair follicles are documented to exert pressure in matter in its path causing displacement; and in one case a flash of light seen as a primary factor in totally reversing turmoil caused by a piezoelectric or pressure induced maneuver. As an incidental finding: The hair shaft is also found to express one-sided magnetic fields similar to inanimate magnets inhibiting human blood issue fibrin formation (clot formation). CONCLUSIONS Presented is a mini-review of biological tissue previously found to emit magnetic fields, now also expressed as light. The light is displayed shown as a “flash” or a “stream”, in both instances displacing matter in its path. The light flash also appears to be a primary factor in bringing equilibrium into the piezoelectric disturbed bioelectromagnetic field. Question arise: What is/are the biological/molecular consequences of living tissue under stress emitting light energy? Why is the hair shaft bioelectromamagnetic field shown in a contralateral fashion, this when the hair follicle is not? Further research is recommended.